Pentingnya Budaya Organisasi, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai - Indah Sari; Fajar Rezeki Ananda Lubis; Nasib Nasib (IPM2KPE, 2023)
This research aims to examine the influence of Organizational Culture, Work Motivation and Work Environment on Employee Performance both partially and simultaneously. The research method used is quantitative. The population and sample in this research were 32 employees. The research results show that organizational culture, work motivation and work environment simultaneously and partially have a positive and significant effect on employee performance. The conclusion of the research is that improving organizational culture, work motivation and work environment can encourage maximum employee performance. Keywords: Organizational Culture, Performance Motivation, Environment